Bergy Bit and Melt Water Trajectories in Godthåbsfjord (SW Greenland) Observed by the Expendable Ice Tracker - Carlson, Daniel F.; Boone, Wieter; Meire, Lorenz; Abermann, Jakob; Rysgaard, Søren (Frontiers in Marine Science, 2017)
Icebergs and bergy makes up a significant component of the total freshwater flux from the Greenland Ice Sheet to the ocean. Observations of iceberg trajectories are biased towards larger icebergs and, as a result, the drift characteristics of smaller icebergs and bergy bits are poorly understood. In an attempt to fill this critical knowledge gap, we developed the open-source EXpendable Ice TrackEr (EXITE). EXITE is a low-cost, satellite-tracked GPS beacon capable of high-resolution temporal measurements over extended deployment periods. Furthermore, EXITE can transform to a surface drifter when its host iceberg capsizes or fragments. Here we describe basic construction of an EXITE beacon and present results from a deployment in Godthåbsfjord (SW Greenland) in August 2016. Overall, EXITE trajectories show out-fjord surface transport, in agreement with a simple estuarine circulation paradigm. However, eddies and abrupt wind-driven reversals reveal complex surface transport pathways at time scales of hours to days.